Controle da temperatura de transformação de fase em uma liga niti através do tratamento térmico de betatização - Barbosa, Marcos Paulo Simões (Universidade Federal Rural do Semi-Árido, 2018)
The use of shape memory alloys, especially the NiTi alloy, has been increasingly frequent, covering a wide range of applications in a wide range of fields, including orthodontics and industry, for use in many types of sensors. Therefore, the studies of this type of material, in order to improve its properties, have gained notoriety in engineering. Concerning NiTi alloys with shape memory effect, one parameter of extreme importance is the phase transformation temperature. It should be noted that this data, provided by the manufacturer, has presented inconsistencies with the actual values, causing problems in the use of the material, since it can change significantly as a consequence of small variations of composition and/or presence of alloying elements. Based on this, the objective of this work is to study and evaluate the effect of the heat treatment of betatization in a commercial NiTi alloy, seeking the modification of the phase transformation temperatures, in order to increase its range of use and to adapt it to the working temperature of specific applications. For this, a bibliographic research was carried out on the commercial applications of NiTi alloys, as well as their properties and characteristics; and on the thermal treatment of betatization, mainly the parameters and equipment used. The alloy was then thermally treated at temperatures of 350, 400 and 450°C with times of 30, 60 and 120 minutes for each temperature. After the heat treatment, the commercial NiTi alloy was characterized by the electrical resistance test as a function of temperature to verify the phase transformation temperature of the material, followed by the mechanical characterization by means of tensile tests, to check how the variation of the transformation temperature affects the mechanical and elastic properties of the alloy. As a result, it has been observed that the heat treatment of betatatization is effective to modify the phase transformation temperature of an NiTi alloy with shape memory; and the highest temperature changes were obtained in the treatments for 60 and 120 minutes at 350 ° C, obtaining a good combination of mechanical and elastic properties.
Monografia
Keywords: Liga NiTi; Memória de forma; Tratamento térmico; Transformação de fase; RET; NiTi Alloy; Shape memory; Heat treatment; Phase transformation; ENGENHARIAS::ENGENHARIA MECANICA